Five stages of grief in C.S. Lewisâ€™ Novel A Grief Observed - Hidayatul Nurjanah (Jurnal CULTURE (Culture, Language, and Literature Review), 2023)
Death is inevitable, inapprehensible, yet it is the most trustworthy experience by human. People have their own various ways to encounter deaths, some by witnessing the death of others, some by reading fictional stories. Death and literature has close relationship as the literary genres portray deaths in various perspectives, such as death is praised in Classics, death is tragic in Romantics, and death is a part of life in postmodern literature. However, the attitude of people towards death and grief are vary. This research aims at finding the stages of grief (death and dying) using KÃ¼bler-Ross theory in C. G. Lewis novel A Grief Observed (1961). This research is qualitative using content analysis approach. The data were gathered through words, phrases, and sentences contained in the novel. The findings shows that the main charater, Lewis, finally succeed managing the whole five stages such as denial, anger, bargaining, depression, acceptance. Moreover, with his acceptance of the death of his wife, he can capture the world in more meaningful ways and find peace in his heart. This is also strengthen that literature can be a media for consolation from suffering since this novel is based on true life story by the author himself.